(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
Contextualization Outsourcing is a global phenomenon that has intensified with globalization and productive restructuring, significantly altering the ways in which work is organized. From a national perspective, the concept of outsourcing was consolidated in the second half of the 20th century, reaching a new level with the 2017 Labor Reform. Laws No. 13,429/2017 and No. 13,467/2017 introduced the possibility of unrestricted outsourcing and the flexibilization of rights, which reignited the debate over whether such changes represent a modernization of labor relations or a social setback. In this context, it is essential to reflect on the impacts of flexibilization on the precariousness of working conditions and the effectiveness of fundamental workers’ rights. Objectives This article aims to critically analyze the phenomenon of outsourcing from the perspective of Brazilian labor legislation, especially since the 2017 Labor Reform. Therefore, it seeks to understand whether the regulatory flexibility introduced by Laws No. 13,429/2017 and No. 13,467/2017 represents progress toward productive modernization or a process of precarious employment relations and the erosion of workers’ social rights. Methodology This research is qualitative in nature, based on documentary and bibliographic sources. Legal provisions from Laws No. 13,429/2017 and No. 13,467/2017 were used, as well as doctrinal works and scientific articles by authors such as Sérgio Pinto Martins. The theoretical and normative analysis was conducted critically, articulating legal, historical, and social foundations to examine the consequences of labor flexibilization in the contemporary Brazilian context. Results The analysis demonstrated in practice that the changes introduced by the Labor Reform did not promote the promised modernization of labor relations, but rather the expansion of precarious practices and the systematic erosion of workers’ rights. Legal provisions were identified that reduce workers’ legal protection, such as the limit on compensation for non-pecuniary damages (Art. 223-G), the prevalence of negotiated over legislated provisions (Art. 611-A), the end of mandatory union dues (Art. 582), and the expansion of outsourcing for core activities (Law No. 13,429/2017). These mechanisms transfer risks to workers, weaken unions, and consequently exacerbate inequality in labor relations. Conclusions Based on the research conducted, we conclude that the 2017 Labor Reform represented a regulatory setback because, under the guise of modernization, it legitimized the flexibilization and deregulation of historically established labor rights. Unrestricted outsourcing and the changes introduced to the Consolidation of Labor Laws (CLT) intensified the precariousness of working conditions and compromised the principle of human dignity. Instead of promoting social justice, the reforms strengthened the logic of employer disengagement and the transfer of economic risks to workers, cementing an unequal and unstable labor model in contemporary Brazil. Keywords: Labor Reform. Flexibilization. Precariousness. Fundamental Rights. Unrestricted Outsourcing.